Robust current-mode control of bridgeless single-switch SEPIC PFC converter - Humam Al-Baidhani; Abdullah Sahib (Institute of Advanced Engineering and Science, 2023)
In this paper, the nonlinear model of the bridgeless single-switch ac-dc single-ended primary-inductor converter (SEPIC) in discontinuous conduction mode is derived. In addition, a robust control method is introduced to accommodate the variations in input voltage and load current. The current-mode controlled power converter is designed to operate in buck and boost modes. The proposed closed-loop SEPIC converter is simulated in MATLAB to validate the design approach. The current-mode control scheme is also compared with the conventional voltage-mode controller. It is confirmed that the proposed control scheme exhibits precise tracking performance and enhanced transient response under large disturbances.